2011
DOI: 10.5194/adgeo-29-51-2011
|View full text |Cite
|
Sign up to set email alerts
|

A hydrologic post-processor for ensemble streamflow predictions

Abstract: Abstract. This paper evaluates the performance of a statistical post-processor for imperfect hydrologic model forecasts. Assuming that the meteorological forecasts are wellcalibrated, we employ a "General Linear Model (GLM)" to post-process simulations produced by a hydrologic model. For a particular forecast date, the observations and simulations from an "analysis window" and hydrologic model forecasts for a "forecast window", the GLM Post-Processor (GLMPP) is used to produce an ensemble of predictions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 27 publications
1
53
0
1
Order By: Relevance
“…The resulting probability distribution is deseribed by a complete density funetion (e.g., Krzysztofowiez 1999; Seo et al 2006;Montanari and Grossi 2008;Todini 2008;Bogner and Pappenberger 2011) or several thresholds of the distribution (e.g., Solomatine and Shrestha 2009;. Examples of postproeessing teehniques for hydrologie ensemble predietion systems include error correction based on the last known forecast error (Velazquez et al 2009), an autoregressive error correction using the most recent modeled error Hopson and Webster 2010; in the latter, postprocessing is also applied to multimodel ensembles), bias correction similar to the MEFP temperature methodology for long-term ESP streamflow ensembles (Wood and Schaake 2008), a Bayesian postprocessor for ensemble streamflow forecasts (Reggiani et al 2009), error correction for multiple temporal scales based on wavelet transformation (Bogner and Kalas 2008;Bogner and Pappenberger 2011), and a generalized linear regression model using multiple temporal scales (Zhao et al 2011). To help establish the reliability of different statistical postprocessors and predictors under varied forecasting conditions, the HEPEX project includes an initiative to intercompare postprocessing techniques in order to develop recommendations for their operational use in hydrologie ensemble prediction systems (van Andel et al 2012).…”
Section: Hydrologic Ensemble Postproces-sormentioning
confidence: 99%
“…The resulting probability distribution is deseribed by a complete density funetion (e.g., Krzysztofowiez 1999; Seo et al 2006;Montanari and Grossi 2008;Todini 2008;Bogner and Pappenberger 2011) or several thresholds of the distribution (e.g., Solomatine and Shrestha 2009;. Examples of postproeessing teehniques for hydrologie ensemble predietion systems include error correction based on the last known forecast error (Velazquez et al 2009), an autoregressive error correction using the most recent modeled error Hopson and Webster 2010; in the latter, postprocessing is also applied to multimodel ensembles), bias correction similar to the MEFP temperature methodology for long-term ESP streamflow ensembles (Wood and Schaake 2008), a Bayesian postprocessor for ensemble streamflow forecasts (Reggiani et al 2009), error correction for multiple temporal scales based on wavelet transformation (Bogner and Kalas 2008;Bogner and Pappenberger 2011), and a generalized linear regression model using multiple temporal scales (Zhao et al 2011). To help establish the reliability of different statistical postprocessors and predictors under varied forecasting conditions, the HEPEX project includes an initiative to intercompare postprocessing techniques in order to develop recommendations for their operational use in hydrologie ensemble prediction systems (van Andel et al 2012).…”
Section: Hydrologic Ensemble Postproces-sormentioning
confidence: 99%
“…Within this study, post-processing encompasses a model for correcting the errors of historical simulations and real-time forecasts, as well as the estimation of the model and forecast uncertainty. Especially in the field of hydro-meteorological Ensemble Predictions Systems (EPS), the importance of post-processing has been acknowledged in order to remove systematic bias and increase forecast skill (see for example, Brown and Seo [1], Zhao et al [2] and Hemri et al [3], to name a few). It is also one of the major themes of the international initiative called HEPEX (Schaake et al [4]).…”
Section: Introductionmentioning
confidence: 99%
“…Ensemble model averaging provides alternatives in addition to a single model, especially when there is not enough information to identify the best model or when the data do not favor a particular model (Kadane and Lazar, 2004). Several studies have applied the MME approach to flow prediction or flood forecasting (Renner et al, 2009;Zhao et al, 2011) and one study demonstrated that combining nitrogen predictions of five models gave better predictions than the individual models (Exbrayat et al, 2010). In addition, the LUCHEM study applied an ensemble of 10 watershed models to assess the effects of land use and land cover (LULC) change on hydrology and water quality Huisman et al, 2009;Viney et al, 2009).…”
Section: Introductionmentioning
confidence: 99%